Carrier transport and working mechanism of transparent photovoltaic cells. (March 2022) - Patel, Malkeshkumar; Song, Jungeun; Kim, Dong-Wook; Kim, Joondong
Highlights: Transparent photovoltaics (TPVs) are the transparent power source. Kelvin probe force microscopy reveals the band-band and defect-mediated transitions. Photocarrier collection given by photocurrent-thickness relation and band-diagram. Aesthetic analysis opens visible transparency and aesthetic quality. Onsite power shows windows application as the invisible power generator. Abstract: Transparent photovoltaics (TPVs) enable transparency in visible regime with the conversion of light into electrical energy. TPVs can be used to replace conventional dark solar cells in parts of buildings and vehicles to enable onsite power generation. For commercial applications, the goal is to ensure human visibility through TPVs while harvesting the maximum output power. However, these two goals are in conflict, and resolving this is a challenging task. Here, we examine TPV devices (TPVDs) using Kelvin probe force microscopy (KPFM) to reveal optoelectronic processes and decisive factors for high-performance devices. TPVDs are based on hybrid heterostructures of metal-oxides with metal-nanowires that possess a high-visible transmittance (63%) with large-area devices. The KPFM studies on ZnO/NiO TPVDs provide evidence of band-to-band photovoltage and defect-mediated photoexcitation at the UV and visible regimes, respectively, which strongly suggests further TPV enhancements can be achieved. Extensive investigation on TPV features was given for light absorption, carrier movement and optical transmittance. Furthermore, this study demonstrates onsite power production using a TPV array, which supplies the electric power to a DC motor (1.5 mW) at a power conversion efficiency of 4.725%. Due to their inherent transparency, TPVs can be applied in windows as on-demand invisible power generators. Graphical abstarct: Image, graphical abstract .